IgE and IgG B cell traffic in a low-dose Gal d1, 2, 3 allergy model - G. V. Fattakhova; A. O. Makarova; M. V. Konovalova; E. I. Kashirina; O. D. Kotsareva; P. S. Okara; E. V. Matushevskaya; E. V. Svirshchevskaya (Медицинская иммунология, 2024)
Type I allergy is mediated by the formation of IgE antibodies to proteins secreted by nonreplicating microorganisms (plant pollen, house dust mites, etc.) that enter the mucous membranes in very low concentrations. The mechanisms and localization of naive B cells’ switching to IgE production have not been fully determined. The aim of this work was to determine the switching site of B cells and the traffic of IgEproducing B cells in mice immunized with a low dose of equimolar mixture of egg proteins Gal d1, Gal d2, and Gal d3. Allergens in saline solution were injected into the withers of mice 9-10 times with an interval of 2-3 days; the total dose was 2.7 µg/mouse. The production of IgE to Gal d proteins in the blood and by B cells isolated from the withers, draining lymph nodes, spleen, and bone marrow of immune mice was analyzed in dynamics after cessation of sensitization. Both in blood and in in vitro cultures, the dominance of IgE changed from the recognition of the LMW Gal d2 during the sensitization of mice to the HMW Gal d3 after sensitization was discontinued. In this model, an IgG memory response appeared only a month after the end of sensitization and recognized only Gal d3. In vitro cultures showed that B cells switched to IgE production locally in the withers with low traffic to the spleen. In the blood serum, IgE titers for all Gal d proteins decreased after the cessation of sensitization and persisted for a long time. A month after the cancellation of the sensitization, a pool of B cells producing IgE in vitro appeared in the spleen. These B-cells died after 20-30 days as no in vitro IgE production was observed later than 85-90 days. The results obtained allowed us to draw several conclusions. B cells switch to IgE synthesis locally at the site of allergen injections. The response was two-phase: LMW Gal d2 was recognized in the early response, while HMW Gal d3 was recognized in the late phase. In this model, the IgG response to HMW Gal d3 was clearly dominant. In conclusion, it has been shown that when the immune system recognizes a mixture of proteins originating from some allergen, the dominance of proteins recognized by both IgE and IgG is observed. Since allergy patients most often do not have IgG antibodies, it can be assumed that in this case an acute phase response, supported by antigen intake, is observed, in which LMW allergens are recognized.